A spherical silicon-aluminum carrier and preparation method thereof

By introducing silicon into the γ-Al2O3 carrier and adopting an oil-in-water emulsion molding process, spherical silicon-aluminum support was prepared, which solved the problem of the reduction in the activity of the carrier at high temperatures, and achieved efficient catalytic performance and environmentally friendly preparation process.

CN116474840BActive Publication Date: 2025-04-08CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202210039908.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-13
Publication Date
2025-04-08
Estimated Expiration
2042-01-13

AI Technical Summary

Technical Problem

The existing γ-Al2O3 carrier is prone to sintering and α-phase change when used at high temperatures, resulting in a decrease in specific surface area and a decrease in catalyst activity. The preparation process is complicated and contaminating.

Method used

A spherical silicon-aluminum carrier was prepared by adding a curing agent, an emulsifier, a polyol and an organic phase to the silicon-containing pseudo-thin hydrocephalassol, and then stirring it to form an oil-in-water emulsion.

Benefits of technology

The prepared spherical silicon-aluminum support has the characteristics of good roundness, low stacking density and high crushing strength. It is suitable for noble metal catalyst support, without pollution in the process, low cost, and shows high propane conversion and propylene selectivity in the propane-to-propylene reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116474840B_ABST
    Figure CN116474840B_ABST
Patent Text Reader

Abstract

The invention discloses a spherical silica-alumina carrier and a preparation method thereof. The preparation method of the spherical silica-alumina carrier comprises: adding a curing agent solution, an emulsifier, a polyol and an organic phase to a silicon-containing pseudo-boehmite sol, respectively, adding water under stirring to prepare an oil-in-water (O / W) emulsion, then dropping it into an oil column to form, washing, drying and roasting to obtain a spherical silica-alumina carrier. The spherical silica-alumina carrier prepared by the method has the characteristics of good roundness, low bulk density, high crushing strength, etc., can be used as a precious metal catalyst carrier, the process has no discharge of pollutants, no environmental pollution, and low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a spherical silica-alumina carrier and a preparation method thereof, in particular to a spherical silica-alumina carrier suitable for a fluidized bed and a noble metal catalyst and a preparation method thereof. Background Art

[0002] The shape and size of catalyst particles are generally determined according to the requirements of the reactor used in industrial production. At present, there are four types of reactors commonly used in industry: fixed bed, fluidized bed (boiling bed), suspended bed and moving bed. Fixed bed reactors often use spherical, cylindrical strip, three-leaf clover, four-leaf clover and sheet catalysts. Moving bed reactors often use large-particle spherical catalysts. Fluidized bed reactors generally use spherical or strip catalysts with smaller particles.

[0003] Spherical catalysts have the advantages of good flow properties, high filling coefficient, uniform fluid distribution, low resistance, small pressure drop, etc., and are widely used in the technology of dehydrogenation of low-carbon alkanes to produce olefins.

[0004] At present, the catalyst for dehydrogenation of low-carbon alkanes to olefins is mainly made of γ-Al2O3 carrier loaded with active component Pt and other additives, such as EP100222A, CN1185994A, etc. However, since the dehydrogenation reaction is carried out at a high temperature of about 600°C, the high reaction temperature often causes a large amount of carbon deposits on the catalyst. As the catalyst is used for a longer time, the catalyst needs to be regenerated by high-temperature carbonization for many times, which causes the γ-Al2O3 carrier to easily sinter and α-phase change, causing the carrier specific surface area to drop significantly, the pore structure to be destroyed, and the catalyst active components to aggregate, and the catalyst activity to drop seriously. Therefore, it is necessary to further modify the γ-Al2O3 carrier to make the catalyst have higher thermal stability.

[0005] CN112973771A discloses a spherical catalyst carrier containing molecular sieve and alumina and its preparation and application. The catalyst carrier is prepared by precipitating an inorganic aluminum salt with ammonia water and acidifying to obtain a sol, adding a ball-milled mixed solution of pseudo-boehmite and molecular sieve and a sol modification aid to the sol, then dropping the sol in an oil-ammonia column to form a ball for aging, and finally washing, drying and calcining to obtain a composite small ball with high strength and large specific surface area. The method is to mix the suspension slurry obtained by ball-milling pseudo-boehmite and molecular sieve with a dilute sol and then peptize again, which will result in the disadvantage of uneven dispersion of molecular sieve. At the same time, the doping of solid molecular sieve will also lead to a decrease in carrier strength.

[0006] CN105478100A discloses a method for preparing silicon-containing γ-Al2O3 beads. The method is to stir and slurry pseudo-boehmite dry rubber powder and deionized water, add dilute nitric acid for acidification, then add urea and a predetermined amount of sodium silicate solution, stir for 5 hours, add kerosene and fatty alcohol polyoxyethylene ether and stir for 5 hours, drop the beads into an oil-ammonia column to form the beads, solidify the wet beads in ammonia water for 2 hours, then filter, rinse with deionized water, dry, and roast to obtain silicon-containing γ-Al2O3 beads. In the preparation process of the method, the silicon source is a sodium silicate solution, and its Na + It is difficult to wash and can be easily brought into the carrier as impurities, affecting the performance of the catalyst. At the same time, it forms droplets in the oil-ammonia column and the wet balls solidify in ammonia water, which is not conducive to operation and causes pollution to the environment.

[0007] CN104289220A discloses a preparation method and application of a low-carbon alkane dehydrogenation catalyst with high thermal stability. The carrier preparation method is to add an aluminum source to an alkaline aqueous solution, stir, continue to drip an alkaline aqueous solution to adjust the pH of the mixed solution to 7-14, filter, wash with deionized water, add dilute nitric acid to form a sol, then add a silicon source, stir, filter, age for 10-48 hours, drop to form a ball, then dry and roast to obtain a γ-Al2O3 ball containing Si element; or to add an aluminum source to an alkaline aqueous solution, stir, continue to drip an alkaline aqueous solution to adjust the pH of the mixed solution to 7-14, filter, wash with deionized water, add dilute nitric acid to form a sol, stir, filter, age for 10-48 hours, drop to form a ball, then dry and roast to obtain a γ-Al2O3 ball, then immerse the γ-Al2O3 ball in an aqueous solution or ethanol solution of a silicon source at 60-120°C for 2-6 hours, then dry and roast to obtain a γ-Al2O3 ball containing Si element. The disadvantages of this method are that the preparation cycle is long and the process is complicated. At the same time, if the inorganic silicon source used is difficult to wash, Na + It is easy to be brought into the carrier as impurities, affecting the performance of the catalyst, and the organosilicon source will cause pollution to the environment. Summary of the invention

[0008] In view of the shortcomings of the prior art, the present invention provides a spherical silica-alumina carrier and a preparation method thereof. The spherical silica-alumina carrier prepared by the method has the characteristics of good roundness, low bulk density, high crushing strength, etc., and is suitable for being a precious metal catalyst carrier. The process does not discharge pollutants, does not pollute the environment, and has low cost.

[0009] The first aspect of the present invention provides a method for preparing a spherical silica-alumina carrier, comprising:

[0010] A curing agent solution, an emulsifier, a polyol and an organic phase are added to a silicon-containing pseudo-boehmite sol respectively, and water is added under stirring to prepare an oil-in-water (O / W) emulsion, which is then dropped into an oil column for molding, washed, dried and calcined to obtain a spherical silica-alumina carrier.

[0011] Furthermore, the method for preparing the silicon-containing pseudo-boehmite sol comprises:

[0012] (1) adding a first alkaline solution into a first reaction kettle, introducing a mixed gas containing carbon dioxide to react, and making the pH value of the system be 2 to 4;

[0013] (2) adding bottom water to the second reaction kettle, heating to the reaction temperature, and then adding the second alkaline solution and the material obtained in step (1) to the second reaction kettle in parallel to react;

[0014] (3) aging the slurry obtained after the reaction in step (2), filtering and washing after the aging to obtain a wet filter cake containing silicon-containing pseudo-boehmite;

[0015] (4) adding water to the wet filter cake obtained in step (3) to prepare a slurry, and then adding a peptizing agent to peptize the slurry to obtain a silicon-containing pseudo-boehmite sol.

[0016] Furthermore, in step (1), the first alkaline solution is a mixed solution of water glass and an aluminum-containing alkaline solution; the aluminum-containing alkaline solution is one or both of a sodium aluminate solution or a potassium aluminate solution, preferably a sodium aluminate solution. The modulus of the water glass is 2.5 to 3.0, and the caustic ratio of the sodium aluminate solution or the potassium aluminate solution is 1.35 to 1.65.

[0017] Furthermore, in step (1), the concentration of water glass in the first alkaline solution is 5 to 90 gSiO2 / L in terms of SiO2, and the concentration of sodium aluminate and / or potassium aluminate in the mixed solution is 10 to 30 gAl2O3 / L in terms of Al2O3.

[0018] Furthermore, in step (1), the volume of the first alkaline solution added to the first reactor is 2 / 3 to 3 / 4 of the volume of the first reactor; the volume fraction of carbon dioxide in the carbon dioxide-containing mixed gas is 30% to 70%; and the carbon dioxide-containing mixed gas is a mixed gas of carbon dioxide and air.

[0019] Furthermore, in step (1), the initial reaction temperature of the reaction of the mixed gas containing carbon dioxide is 15 to 65°C. The reaction is an exothermic reaction, and the system temperature gradually increases. The entire reaction process does not require cooling to maintain a low temperature. Generally, the temperature of the slurry at the end of the reaction is 40 to 75°C.

[0020] Furthermore, in step (2), the second alkaline solution is one or both of a sodium aluminate solution and a potassium aluminate solution, preferably a sodium aluminate solution; the concentration of the sodium aluminate solution and / or the potassium aluminate is 130 to 350 g Al2O3 / L, preferably 150 to 250 g Al2O3 / L in terms of Al2O3. The caustic ratio of the second alkaline solution is 1.10 to 1.40, preferably 1.15 to 1.35.

[0021] Furthermore, in step (2), the bottom water added to the second reaction kettle is 1 / 10 to 1 / 5 of the volume of the second reaction kettle.

[0022] Furthermore, in step (2), the material obtained in step (1) is added to the second reaction kettle, and the material addition time is controlled to be 60 to 150 minutes.

[0023] Furthermore, in step (2), the second alkaline solution and the material obtained in step (1) are added to the second reactor in parallel to react, and the pH value is controlled to be 7.5-9.0.

[0024] Furthermore, in step (2), the reaction temperature of the reaction is 40°C to 70°C, preferably 45°C to 65°C.

[0025] Furthermore, in step (2), the reaction is carried out under stirring.

[0026] Furthermore, in step (3), the aging conditions are: temperature of 50°C to 95°C and time of 30min to 120min.

[0027] Furthermore, in step (3), the washing may be carried out by conventional washing methods in the art, preferably by washing with deionized water at 50° C. to 80° C. until the mixture becomes neutral.

[0028] Furthermore, in step (3), the solid content of the obtained silicon-containing pseudo-boehmite wet filter cake is 35wt% to 45wt%.

[0029] Furthermore, in step (4), the wet filter cake obtained in step (3) is mixed with water and beaten to obtain a slurry; the peptizing agent is one or more of nitric acid, acetic acid, and citric acid, preferably nitric acid; and the mass concentration of the peptizing agent is 50% to 70%.

[0030] Furthermore, in step (4), the amount of the peptizing agent added is 1 wt% to 10 wt% of the solid content in the silicon-containing pseudo-boehmite wet filter cake, preferably 2 wt% to 8 wt%.

[0031] Furthermore, in step (4), the solid content of the silicon-containing pseudo-boehmite sol is 30 wt% to 35 wt%.

[0032] Furthermore, in the preparation method of the spherical silica-alumina carrier, the curing agent solution is a solution of one or more of hexamethylenetetramine and urea, preferably a hexamethylenetetramine solution; the mass concentration of the curing agent solution is 30% to 50%; the amount of the curing agent added is 1wt% to 15wt% of the solid content in the silica-containing pseudo-boehmite sol, preferably 2.5wt% to 12wt%.

[0033] Furthermore, in the preparation method of the spherical silica-alumina carrier, the emulsifier is a non-ionic emulsifier, specifically selected from at least one of polyoxyethylene sorbitan monolaurate and fatty alcohol polyoxyethylene ether; the hydrophile-lipophile balance (HLB) value of the emulsifier is 13 to 20, preferably 15 to 18, and the amount of the emulsifier added is 0.2wt% to 2.0wt% of the solid content in the silica-containing pseudo-boehmite sol, preferably 0.5wt% to 1.5wt%.

[0034] Furthermore, in the preparation method of the spherical silica-alumina carrier, the polyol is one or more of 1,3-propylene glycol, 1,3-butanediol, 1,4-butanediol, 1,2-propylene glycol, 1-pentanol, and polyethylene glycol (400), and the amount of the polyol added is 0.1wt% to 1.0wt% of the solid content in the silicon-containing pseudo-boehmite sol, preferably 0.2wt% to 0.8wt%.

[0035] Furthermore, in the preparation method of the spherical silica-alumina carrier, the organic phase is one or more of white oil or diesel; the amount of the organic phase added is 7.0wt% to 13.0wt% of the solid content in the silicon-containing pseudo-boehmite sol, preferably 7.5wt% to 12.5wt%.

[0036] Furthermore, in the method for preparing the spherical silica-alumina carrier, the mass of the added water is 0.5 to 1.5 times the solid content of the silicon-containing pseudo-boehmite sol.

[0037] Furthermore, in the preparation method of the spherical silica-alumina carrier, the stirring speed is 1000 to 4000 revolutions per minute; and the mass content of aluminum oxide in the oil-in-water (O / W) emulsion is 15% to 25%.

[0038] Furthermore, in the preparation method of the spherical silica-alumina carrier, the medium oil used in the oil column is one of white oil or diesel, preferably white oil, and the kinematic viscosity of the white oil at 40°C is 20-40 mm 2 / s, preferably 25-35mm 2 / s; the molding temperature is 90°C to 110°C, preferably 95°C to 105°C.

[0039] Furthermore, in the preparation method of the spherical silica-alumina carrier, the molding is carried out in an oil column, and the water-in-oil emulsion is dripped into the oil column, and the inner diameter of the dripper used is 0.4 mm to 2.0 mm.

[0040] Furthermore, in the preparation method of the spherical silica-alumina carrier, the washing is divided into two steps, namely, firstly, the molding material is washed with a mixed solution of at least one solvent selected from petroleum ether, cyclohexane or toluene and anhydrous ethanol in a volume ratio of 1: (1 to 3) to remove the medium oil of the molding material, and then the mixed solution on the molding material is washed with deionized water at a temperature of 70°C to 90°C to remove the mixed solution.

[0041] Furthermore, in the preparation method of the spherical silica-alumina carrier, the drying temperature is 100° C. to 150° C., and the drying time is 6 to 10 hours; the calcination temperature is 550° C. to 750° C., and the calcination time is 1 to 4 hours.

[0042] The second aspect of the present invention provides a spherical silica-alumina carrier obtained by the above preparation method.

[0043] Furthermore, the properties of the spherical silica-alumina carrier are as follows: pore volume>0.68mL / g, preferably 0.70mL / g to 0.95mL / g; specific surface area>180m 2 / g, preferably 185m 2 / g~240m 2 / g; pore distribution: the pore volume of pores with a pore diameter of less than 10nm accounts for less than 5.5% of the total pore volume, preferably less than 5.0%, the pore volume of pores with a pore diameter of more than 20nm accounts for less than 7.5% of the total pore volume, preferably less than 7.0%; the diameter of the carrier particles is 1.6-2.2mm, preferably 1.7-2.0mm, the bulk density is 0.60-0.68g / mL, the crushing strength is >50N / particle, preferably 55N / particle-75N / particle; the volume occupied by the fine spherical cavity is 10%-35% of the volume of the carrier.

[0044] Furthermore, the mass content of SiO2 in the spherical silica-alumina carrier is 1.0-35.0%.

[0045] The third aspect of the present invention provides the use of the spherical silica-alumina carrier described in the second aspect as a catalyst carrier in the production of propylene from propane.

[0046] Compared with the prior art, the advantages of the present invention are:

[0047] (1) The silicon-containing pseudo-boehmite wet filter cake prepared by the present invention has low gibbsite content, high crystallinity, and easy-to-adjust silicon content, and the silicon-containing alumina obtained by calcination has a large pore volume and pore diameter; at the same time, the silicon-containing pseudo-boehmite wet filter cake prepared by the present invention has a high peptization index, which provides a guarantee for preparing a carrier with high lateral compressive strength;

[0048] (2) In the preparation method of the present invention, the first alkaline solution first reacts with the mixed gas containing carbon dioxide, and the pH value of the system is adjusted to a specific range, which is beneficial to improving the crystallinity of the product. In the co-current reaction with the second alkaline solution, the crystals formed after the reaction of the first alkaline solution with carbon dioxide can be used as crystal nuclei for the co-current reaction, so that the prepared silicon-containing pseudo-boehmite crystals are enlarged, forming a larger pore volume and a suitable pore distribution;

[0049] (3) In the preparation method of the present invention, the first alkaline solution is first reacted with a mixed gas containing carbon dioxide, and the pH value of the system is adjusted to acidic, so that the Na + The precursor of silicon dioxide is in a free state, while the precursor of silicon dioxide is combined with or adsorbed on the pseudo-boehmite grains, making the subsequent + Washing is easier and saves washing water;

[0050] (4) The carrier raw material of the present invention is prepared into an oil-in-water (O / W) emulsion, and the organic phase is dispersed in the emulsion in the form of fine droplets. During the molding process, the emulsion droplets enter the medium oil and automatically shrink into a spherical shape under the action of surface tension. The gelling agent in the emulsion is decomposed by heat, and the released alkaline gas causes the emulsion to solidify into small spheres. At the same time, the stability of the emulsion is destroyed due to temperature reasons, and the organic phase therein is dissolved in the medium oil. Uniformly sized fine spherical cavities are formed on the surface and inside of the solidified small spheres, while the continuous phase silicon-containing aluminum hydroxide sol does not change. Therefore, the bulk ratio is reduced, while the strength is not affected;

[0051] (5) In the process of preparing the oil-in-water (O / W) emulsion from the carrier raw material of the present invention, polyol is added to improve the emulsifying ability of the emulsifier and promote the uniform dispersion of the organic phase to form fine droplets. At the same time, the size and number of the fine spherical cavities can be controlled by controlling the stirring speed and the amount of organic phase added;

[0052] (6) The preparation method of the present invention is simple, easy to operate and pollution-free;

[0053] (7) The spherical silica-alumina carrier obtained by the preparation method of the present invention is used in the propane to propylene reaction, has a high propane conversion rate and propylene selectivity, the total carbon deposit amount of the catalyst is low after 35 hours of reaction, and has good stability and good reaction performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 This is a SEM image of the spherical silicon-aluminum carrier prepared in Example 1 of the present invention;

[0055] Figure 2 This is a SEM image of the spherical silicon-aluminum carrier prepared in Example 3 of the present invention;

[0056] Figure 3 This is a SEM image of the spherical silicon-aluminum carrier prepared in Example 5 of the present invention;

[0057] Figure 4 This is a SEM image of the spherical silicon-aluminum carrier prepared in Comparative Example 1 of the present invention;

[0058] Figure 5 This is a SEM image of the spherical silicon-aluminum carrier prepared in Comparative Example 2 of the present invention;

[0059] Figure 6 This is the SEM image of the spherical silica-alumina carrier prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0060] The following examples further illustrate the preparation method and effect of the spherical silica-alumina carrier in the present invention. The examples are implemented based on the technical solution of the present invention, and provide detailed implementation methods and specific operation processes, but the protection scope of the present invention is not limited to the following examples.

[0061] The experimental methods in the following examples, unless otherwise specified, are all conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, were purchased from conventional biochemical reagent stores.

[0062] In the present invention, a Japanese Hitachi S-4700 field emission scanning electron microscope (SEM) is used to observe the morphology and particle size of the carrier.

[0063] In the present invention, the ASAP2020 fully automatic physical adsorption instrument produced by Micromeritics Corporation of the United States is used to test the nitrogen adsorption-desorption curve of the sample at -196°C to determine the specific surface area, pore volume and pore size distribution.

[0064] In the present invention, the crushing strength is tested by a ZQJ-III intelligent particle strength testing machine manufactured by Dalian Zhiqu Testing Machine Factory, and the average value of crushing ten spherical carriers is tested.

[0065] In the present invention, the bulk density is the weight of the spherical carrier loaded into a 100 mL measuring cylinder.

[0066] In the present invention, the method for testing the volume of the carrier micro-spherical cavity is to prepare a solid spherical carrier with the same pore volume, particle size and true density as the micro-spherical cavity carrier, and respectively measure 100 mL of the micro-spherical cavity carrier and the solid spherical carrier with a 100 mL measuring cylinder and weigh and measure them, then add deionized water to the measuring cylinder to the 100 mL scale and measure the added water volume, then the total volume of the micro-spherical cavity is the amount of deionized water added to the solid spherical carrier measuring cylinder minus the total pore volume of 100 mL of the solid spherical carrier and the amount of deionized water added to the micro-spherical cavity carrier measuring cylinder minus the total pore volume of 100 mL of the micro-spherical cavity carrier, and the volume of the carrier occupied by the micro-spherical cavity is the total volume of the micro-spherical cavity divided by the weight of 100 mL of the micro-spherical cavity carrier and then divided by the true density of the micro-spherical cavity carrier.

[0067] Example 1

[0068] Add 3500 mL of a mixed solution of water glass with a modulus of 2.8 and a concentration of 50 g SiO2 / L and a sodium aluminate solution with a caustic ratio of 1.45 and a concentration of 25 g Al2O3 / L into a 5000 mL first reaction kettle, and then introduce a mixed gas of carbon dioxide and air containing 55% carbon dioxide by volume to reduce the pH value of the system to 3.4. The temperature of the material at the end of the reaction is 55°C;

[0069] 1500 mL of bottom water was added to a 10000 mL second reaction kettle, and the stirring and heating devices were started. When the temperature rose to 65° C., the above materials were added to the second reaction kettle at a flow rate of 35 mL / min, and a sodium aluminate solution with a concentration of 180 gAl2O3 / L and a caustic ratio of 1.25 was added in parallel. The pH value of the slurry in the second reaction kettle was controlled to be 8.0 by adjusting the flow rate of the sodium aluminate solution, and the temperature of the slurry in the second reaction kettle was kept constant. The reaction was terminated after the above materials were used up, and the slurry was aged at 90° C. for 80 min. After the aging was completed, it was washed with deionized water at a temperature of 70° C. until neutral, and filtered to obtain a silicon-containing pseudo-boehmite wet filter cake with a solid content of 42%.

[0070] Take 238g of the above silicon-containing pseudo-boehmite filter cake, add 68.6g of deionized water, stir and slurry evenly, then add 10.8g of nitric acid solution with a mass concentration of 60% for peptization, and finally prepare a silicon-containing pseudo-boehmite sol with a solid content of 31.5%;

[0071] To the above 317.5 g of silica-containing pseudo-boehmite sol were added in sequence 20 g of a 40% hexamethylenetetramine solution, 0.8 g of polyoxyethylene sorbitan monolaurate (Tween 20) with an HLB value of 16.7, 0.6 g of 1,3-propylene glycol, and 9 g of white oil, and then 128.3 g of deionized water was added. The stirring speed was adjusted to 3500 rpm and stirring was performed so that the solid content of the finally prepared oil-in-water (O / W) emulsion was 21%.

[0072] The viscosity of the dripper with an inner diameter of 0.8 mm at 40 ° C is 28 mm 2 / s, the above-mentioned water-in-oil (O / W) emulsion was added dropwise to white oil at a temperature of 95°C for molding. The molding material was first washed with a mixed solution of petroleum ether and anhydrous ethanol in a volume ratio of 1:1 to remove the medium oil of the molding material, and then washed with deionized water at a temperature of 85°C, and then dried at 130°C for 8 hours, and calcined at 650°C for 3 hours to obtain the spherical silica-alumina carrier A-1 of the present invention. The analysis results are shown in Table 1, and the SEM results are shown in Table 1. Figure 1 ,pass Figure 1 It can be seen that the carrier of the present invention contains more uniform micro-spherical cavities, which can effectively reduce the packing density of the carrier.

[0073] Example 2

[0074] The other conditions were the same as those in Example 1, except that the concentration of SiO2 in the mixed solution was changed to 75 g / L, the concentration of Al2O3 in the mixed solution was changed to 15 g / L, the volume fraction of carbon dioxide in the mixed gas of carbon dioxide and air was 45%, and the aging temperature was changed to 97°C to obtain the spherical silica-alumina carrier A-2 of the present invention, and the analysis results are shown in Table 1. SEM images and Figure 1 resemblance.

[0075] Example 3

[0076] The other conditions were the same as those in Example 1, except that the stirring speed during the preparation of the oil-in-water (O / W) emulsion was changed to 1500 rpm, and the spherical silica-alumina carrier A-3 of the present invention was obtained. The analysis results are shown in Table 1, and the SEM results are shown in Table 1. Figure 2 .

[0077] Example 4

[0078] The other conditions were the same as those in Example 1, except that the emulsifier was changed to 1.5 g of fatty alcohol polyoxyethylene ether (MOA-15) with an HLB value of 15.0, and 1,3-propylene glycol was changed to 1,3-butylene glycol to obtain the spherical silica-alumina carrier A-4 of the present invention. The analysis results are shown in Table 1. SEM images and Figure 1 resemblance.

[0079] Example 5

[0080] Add 4000mL of water glass with a modulus of 3.0 and a SiO2 concentration of 35g / L and a sodium aluminate mixed solution with a caustic ratio of 1.40 and an Al2O3 concentration of 8g / L into a 5000mL first reaction kettle, and then introduce a mixed gas of carbon dioxide and air with a volume fraction of 45% carbon dioxide to reduce the pH value of the system to 2.5. The temperature of the material at the end of the reaction is 40°C;

[0081] Add 1000 mL of bottom water to a 10000 mL second reaction kettle, start the stirring and heating device, and when the temperature rises to 55° C., add the above materials to the second reaction kettle at a flow rate of 35 mL / min, and simultaneously add a sodium aluminate solution with a concentration of 210 gAl2O3 / L and a caustic ratio of 1.18 in parallel, and control the pH value of the slurry in the second reaction kettle to 8.8 by adjusting the flow rate of the sodium aluminate solution, while keeping the temperature of the slurry in the second reaction kettle constant. After the above materials are used up, the reaction ends, and the slurry is aged at 80° C. for 120 min. After the aging, it is washed with deionized water at a temperature of 75° C. until it is neutral, and filtered to obtain a silicon-containing pseudo-boehmite wet filter cake with a solid content of 37%.

[0082] Take 270g of the above silicon-containing pseudo-boehmite wet filter cake, add deionized water, stir and slurry it evenly, then add 6.2g of nitric acid solution with a mass concentration of 65% for peptization, and finally prepare a silicon-containing pseudo-boehmite sol with a silicon-aluminum mass content of 34%;

[0083] To the above 294.1 g of silica-containing pseudo-boehmite sol were added in sequence 23.4 g of hexamethylenetetramine solution with a mass concentration of 32%, 1.2 g of polyoxyethylene sorbitan monolaurate (Tween 20) with an HLB value of 16.7, 0.3 g of 1,3-propylene glycol, and 7.5 g of white oil, and then deionized water was added. The stirring speed was adjusted to 3500 rpm and stirring was performed so that the solid content of the finally prepared oil-in-water (O / W) emulsion was 18%.

[0084] Use a dripper with an inner diameter of 1.2 mm to move the viscosity to 30 mm at 40 °C 2 / s, the above-mentioned water-in-oil (O / W) emulsion is added dropwise to white oil at a temperature of 105°C for molding. The molding material is first washed with a mixed solution of cyclohexane and anhydrous ethanol in a volume ratio of 1:3 to remove the medium oil of the molding material, and then washed with deionized water at a temperature of 75°C, and then dried at 120°C for 10 hours, and calcined at 700°C for 2 hours to obtain the spherical silica-alumina carrier A-5 of the present invention. The analysis results are shown in Table 1, and the SEM results are shown in Table 1. Figure 3 .

[0085] Comparative Example 1

[0086] Add 3500 mL of a mixed solution of water glass with a modulus of 2.8 and a concentration of 50 g SiO2 / L and a sodium aluminate solution with a caustic ratio of 1.45 and a concentration of 25 g Al2O3 / L into a 5000 mL first reaction kettle, and then introduce a mixed gas of carbon dioxide and air containing 55% carbon dioxide by volume to reduce the pH value of the system to 3.4. The temperature of the material at the end of the reaction is 55°C;

[0087] 1500 mL of bottom water was added to a 10000 mL second reaction kettle, and the stirring and heating devices were started. When the temperature rose to 65° C., the above materials were added to the second reaction kettle at a flow rate of 35 mL / min, and a sodium aluminate solution with a concentration of 180 gAl2O3 / L and a caustic ratio of 1.25 was added in parallel. The pH value of the slurry in the second reaction kettle was controlled to be 8.0 by adjusting the flow rate of the sodium aluminate solution, and the temperature of the slurry in the second reaction kettle was kept constant. The reaction was terminated after the above materials were used up, and the slurry was aged at 90° C. for 80 min. After the aging was completed, it was washed with deionized water at a temperature of 70° C. until neutral, and filtered to obtain a silicon-containing pseudo-boehmite wet filter cake with a solid content of 42%.

[0088] Take 238g of the above silicon-containing pseudo-boehmite filter cake, add 227.4g of deionized water, stir and slurry evenly, then add 10.8g of nitric acid solution with a mass concentration of 60% for peptization, and finally prepare a silicon-containing pseudo-boehmite sol with a solid content of 21%;

[0089] The viscosity of the dripper with an inner diameter of 0.8 mm at 40 ° C is 28 mm 2 / s, the above-mentioned water-in-oil (O / W) emulsion was added dropwise to white oil at a temperature of 95°C for molding. The molding material was first washed with a mixed solution of petroleum ether and anhydrous ethanol in a volume ratio of 1:1 to remove the medium oil of the molding material, and then washed with deionized water at a temperature of 85°C, and then dried at 130°C for 8 hours, and calcined at 650°C for 3 hours to obtain a spherical silica-alumina carrier D-1. The analysis results are shown in Table 1, and the SEM results are shown in Table 1. Figure 4 .

[0090] Comparative Example 2

[0091] Add 3500 mL of a mixed solution of water glass with a modulus of 2.8 and a concentration of 50 g SiO2 / L and a sodium aluminate solution with a caustic ratio of 1.45 and a concentration of 25 g Al2O3 / L into a 5000 mL first reaction kettle, and then introduce a mixed gas of carbon dioxide and air containing 55% carbon dioxide by volume to reduce the pH value of the system to 3.4. The temperature of the material at the end of the reaction is 55°C;

[0092] 1500 mL of bottom water was added to a 10000 mL second reaction kettle, and the stirring and heating devices were started. When the temperature rose to 65° C., the above materials were added to the second reaction kettle at a flow rate of 35 mL / min, and a sodium aluminate solution with a concentration of 180 gAl2O3 / L and a caustic ratio of 1.25 was added in parallel. The pH value of the slurry in the second reaction kettle was controlled to be 8.0 by adjusting the flow rate of the sodium aluminate solution, and the temperature of the slurry in the second reaction kettle was kept constant. The reaction was terminated after the above materials were used up, and the slurry was aged at 90° C. for 80 min. After the aging was completed, it was washed with deionized water at a temperature of 70° C. until neutral, and filtered to obtain a silicon-containing pseudo-boehmite wet filter cake with a solid content of 42%.

[0093] Take 238g of the above silicon-containing pseudo-boehmite filter cake, add 68.6g of deionized water, stir and slurry evenly, then add 10.8g of nitric acid solution with a mass concentration of 60% for peptization, and finally prepare a silicon-containing pseudo-boehmite sol with a solid content of 31.5%;

[0094] To the above 317.5 g of silica-containing pseudo-boehmite sol were added in sequence 20 g of a 40% hexamethylenetetramine solution, 0.8 g of polyoxyethylene sorbitan monolaurate (Tween 20) with an HLB value of 16.7, and 9 g of white oil, and then deionized water was added. The stirring speed was adjusted to 3500 rpm and stirring was performed so that the solid content of the finally prepared oil-in-water (O / W) emulsion was 21%.

[0095] The viscosity of the dripper with an inner diameter of 0.8 mm at 40 ° C is 28 mm 2 / s, the above-mentioned water-in-oil (O / W) emulsion was added dropwise to white oil at a temperature of 95°C for molding. The molding material was first washed with a mixed solution of petroleum ether and anhydrous ethanol in a volume ratio of 1:1 to remove the medium oil of the molding material, and then washed with deionized water at a temperature of 85°C, and then dried at 130°C for 8 hours, and calcined at 650°C for 3 hours to obtain a spherical silica-alumina carrier D-2. The analysis results are shown in Table 1, and the SEM results are shown in Table 1. Figure 5 .

[0096] Comparative Example 3

[0097] Prepare 3500 mL of a mixed solution of aluminum sulfate with a modulus of 2.8, a concentration of 50 g / L in terms of SiO2 and a concentration of 25 g / L in terms of Al2O3, and set aside.

[0098] 1500mL of bottom water was added to a 10000mL reactor, and a stirring and heating device was started. When the temperature rose to 65°C, the obtained aluminum sulfate mixed solution was added to the reactor at a flow rate of 35mL / min, and 180gAl2O3 / L of a sodium aluminate solution with a caustic ratio of 1.25 was added in parallel. The pH value of the slurry in the reactor was controlled to be 8.0 by adjusting the flow rate of the sodium aluminate solution, and the temperature of the slurry in the reactor was kept constant. The reaction was terminated after the mixed solution was used up. The slurry was aged at 90°C for 80min. After the aging was completed, the slurry was washed with deionized water at a temperature of 70°C until neutral, and filtered to obtain a silicon-containing pseudo-boehmite wet filter cake with a solid content of 42%.

[0099] Take 238g of the above silicon-containing pseudo-boehmite filter cake, add deionized water, stir and slurry it evenly, then add 10.8g of nitric acid solution with a mass concentration of 60% for peptization, and finally prepare a silicon-containing pseudo-boehmite sol with a solid content of 31.5%;

[0100] To the above 317.5 g of silica-containing pseudo-boehmite sol were added in sequence 20 g of a 40% hexamethylenetetramine solution, 0.8 g of polyoxyethylene sorbitan monolaurate (Tween 20) with an HLB value of 16.7, and 9 g of white oil, and then deionized water was added. The stirring speed was adjusted to 3500 rpm and stirring was performed so that the solid content of the finally prepared oil-in-water (O / W) emulsion was 21%.

[0101] The viscosity of the dripper with an inner diameter of 0.8 mm at 40 ° C is 28 mm 2 / s, the above-mentioned water-in-oil (O / W) emulsion was added dropwise to white oil at a temperature of 95°C for molding. The molding material was first washed with a mixed solution of petroleum ether and anhydrous ethanol in a volume ratio of 1:1 to remove the medium oil of the molding material, and then washed with deionized water at a temperature of 85°C, and then dried at 130°C for 8 hours, and calcined at 650°C for 3 hours to obtain a spherical silica-alumina carrier D-3. The analysis results are shown in Table 1, and the SEM results are shown in Table 1. Figure 6 .

[0102] Example 6

[0103] The spherical silica-alumina carriers prepared in Examples 1, 3, 5 and Comparative Examples 1, 2, 3 were respectively impregnated with an impregnation solution containing chloroplatinic acid, stannous chloride and hydrochloric acid for 6 hours at a liquid / solid ratio of 2.0 mL / g. After impregnation, they were dried at 120°C for 12 hours and calcined at 600°C for 4 hours to obtain oxidized catalysts A and B. C -1, A C -3.A C -5 and D C -1, D C -2, D C -3, where the metal content analysis results are shown in Table 2.

[0104] 10 ml of oxidized catalyst was loaded into the microreactor and the catalyst activity was evaluated after reduction with hydrogen at 580 °C for 4 hours. A mixture of hydrogen and propane was used as the raw material. The reaction temperature was 625 °C, the reaction pressure was 0.25 MPa, and the propane feed mass space velocity was 6.5 h -1 The reaction was carried out under the conditions of a hydrogen / propane molar ratio of 0.5:1. The propane conversion rate and propylene selectivity of each catalyst at different reaction times are shown in Table 3.

[0105] Table 1 Physical and chemical properties of spherical silica-alumina carriers of Examples and Comparative Examples

[0106]

[0107]

[0108] Table 2 Catalyst metal content analysis results

[0109] serial number <![CDATA[A C -1]]> <![CDATA[A C -3]]> <![CDATA[A C -5]]> <![CDATA[D C -1]]> <![CDATA[D C -2]]> <![CDATA[D C -3]]> Pt, wt% 0.35 0.33 0.35 0.35 0.35 0.35 Sn, wt% 0.75 0.77 0.73 0.75 0.75 0.75

[0110] Table 3 Catalyst evaluation results

[0111]

[0112] As can be seen from Table 3, the catalyst prepared by the carrier of the present invention has a high propane conversion rate and propylene selectivity, the total carbon deposit amount of the catalyst after 35 hours of reaction is low, and it has good stability and good reaction performance.

Claims

1. A method for preparing a spherical silica-alumina carrier, comprising the following steps: Adding a curing agent solution, an emulsifier, a polyol and an organic phase to a silicon-containing pseudo-boehmite sol, respectively, adding water under stirring to prepare an oil-in-water emulsion, then dropping it into an oil column to form, washing, drying and calcining to obtain a spherical silicon-alumina carrier; The preparation method of the silicon-containing pseudo-boehmite sol comprises: (1) adding a first alkaline solution into a first reaction kettle, introducing a mixed gas containing carbon dioxide to react, and making the pH value of the system be 2 to 4; (2) adding bottom water to the second reaction kettle, heating to the reaction temperature, and then adding the second alkaline solution and the material obtained in step (1) into the second reaction kettle in parallel to react; (3) aging the slurry obtained after the reaction in step (2), filtering and washing after the aging to obtain a wet filter cake containing silicon-containing pseudo-boehmite; (4) adding water to the wet filter cake obtained in step (3) to prepare a slurry, and then adding a peptizing agent to peptize the slurry to obtain a silicon-containing pseudo-boehmite sol; In step (1), the first alkaline solution is a mixed solution of water glass and an aluminum-containing alkaline solution; in step (2), the second alkaline solution is one or both of a sodium aluminate solution and a potassium aluminate solution; The curing agent solution is a solution of one or more of hexamethylenetetramine and urea; the emulsifier is selected from at least one of polyoxyethylene sorbitan monolaurate and fatty alcohol polyoxyethylene ether; and the hydrophilic-lipophilic balance value of the emulsifier is 13-20.

2. The preparation method according to claim 1, characterized in that: In step (1), the aluminum-containing alkaline solution is one or both of a sodium aluminate solution and a potassium aluminate solution; the modulus of the water glass is 2.5 to 3.0, and the caustic ratio of the sodium aluminate solution or the potassium aluminate solution is 1.35 to 1.

65.

3. The preparation method according to claim 1, characterized in that: In step (1), the concentration of water glass in the first alkaline solution is 5 to 90 g SiO2 / L in terms of SiO2, and the concentration of sodium aluminate and / or potassium aluminate in the mixed solution is 10 to 30 g Al2O3 / L in terms of Al2O3.

4. The preparation method according to claim 1, characterized in that: In step (1), the volume of the first alkaline solution added to the first reactor is 2 / 3 to 3 / 4 of the volume of the first reactor; the volume fraction of carbon dioxide in the carbon dioxide-containing mixed gas is 30% to 70%; and the carbon dioxide-containing mixed gas is a mixed gas of carbon dioxide and air.

5. The preparation method according to claim 1, characterized in that: In step (2), the reaction temperature is 40°C to 70°C; in step (3), the aging conditions are: temperature is 50°C to 95°C, and time is 30min to 120min.

6. The preparation method according to claim 1, characterized in that: The mass concentration of the curing agent solution is 30% to 50%; the amount of the curing agent added is 1wt% to 15wt% of the solid content in the silicon-containing pseudo-boehmite sol.

7. The preparation method according to claim 1, characterized in that: The amount of the emulsifier added is 0.2wt% to 2.0wt% of the solid content in the silicon-containing pseudo-boehmite sol.

8. The preparation method according to claim 1, characterized in that: The polyol is one or more of 1,3-propylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 1,2-propylene glycol, and polyethylene glycol (400). The amount of the polyol added is 0.1wt% to 1.0wt% of the solid content in the silicon-containing pseudo-boehmite sol.

9. The preparation method according to claim 1, characterized in that: The organic phase is one or more of white oil or diesel; the amount of the organic phase added is 7.0wt% to 13.0wt% of the solid content in the silicon-containing pseudo-boehmite sol; the mass of water added is 0.5 to 1.5 times the solid content in the silicon-containing pseudo-boehmite sol.

10. The preparation method according to claim 1, characterized in that: The stirring speed is 1000-4000 rpm; the mass content of aluminum oxide in the water-in-oil emulsion is 15%-25%; the medium oil used in the oil column is one of white oil or diesel, and the kinematic viscosity of the white oil at 40°C is 20-40mm 2 / s; the molding temperature is 90°C to 110°C; the molding is carried out in an oil column, and the water-in-oil emulsion is dripped into the oil column, and the inner diameter of the dripper used is 0.4mm to 2.0mm.

11. A spherical silica-alumina carrier obtained by the preparation method according to any one of claims 1 to 10.

12. The spherical silica-alumina carrier according to claim 11, characterized in that: The properties of the spherical silica-alumina carrier are as follows: pore volume>0.68mL / g; specific surface area>180m 2 / g; pore distribution: the pore volume of pores with a pore diameter of less than 10nm accounts for less than 5.5% of the total pore volume, and the pore volume of pores with a pore diameter of more than 20nm accounts for less than 7.5% of the total pore volume; the diameter of the carrier particles is 1.6-2.2mm, the bulk density is 0.60-0.68g / mL, and the crushing strength is >50N / particle; the volume occupied by the fine spherical cavity is 10%-35% of the carrier volume.

13. The spherical silica-alumina carrier according to claim 11, characterized in that: The mass content of SiO2 in the spherical silica-alumina carrier is 1.0-35.0%.

Citation Information

Patent Citations

  • Preparation method and application of light alkane dehydrogenation catalyst with high thermal stability

    CN104289220A

  • Method for preparing silicon-containing gamma-Al2O3 microsphere

    CN105478100A

  • Spherical catalyst carrier containing molecular sieves and aluminum oxide as well as preparation and application of spherical catalyst carrier

    CN112973771A

  • Catalyst for producing isobutylene by catalytic dehydrogenation of isobutane and procedure thereof

    CN1185994A

  • Process for dehydrogenating hydrocarbons

    EP0100222A1